(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
Thanks to intensive research in the 90s, the structure of risk factors associated with the development and progression of DN was determined in sufficient detail. The main risk factors include hereditary predisposition, arterial hypertension (AH), and the quality of metabolic control. The occurrence and rate of progression of DN can also vary significantly depending on the level of proteinuria, gender, age, duration of DM, comorbid pathology, body mass index (BMI), treatment and some other 6 clinical factors. However, the search for other predictors of an unfavorable course of DN, in addition to the already known ones, continues intensively. Thus, morphological changes in kidney tissue, which are associated with hyperplastic processes, excessive accumulation of the matrix, with an increase in the volume of the glomerulus and interstitium, and, subsequently, with the development of diffuse nephrosclerosis, are of no small importance in the prognosis of the course of DN and the effect of therapy.